2014
DOI: 10.1159/000358226
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Stimulates and Dexamethasone Inhibits Pulmonary Vascular Development in Congenital Diaphragmatic Hernia Rat Lungs

Abstract: Background: A predictor of neonatal mortality in infants with congenital diaphragmatic hernia (CDH) is disrupted pulmonary vascular development, clinically expressed as pulmonary hypertension. Objective: To determine if prenatal corticosteroids and phosphodiesterase-5 (PDE-5) inhibitors have a beneficial effect on pulmonary vascular development in CDH lungs. Methods: We induced CDH in fetal rats by giving nitrofen. We then exposed them to dexamethasone or to sildenafil. We separated them into three groups: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
3
15
0
1
Order By: Relevance
“…PVR was lower in DH-sildenafil, compared with DH-saline, lambs during the fetal instrumentation period immediately before birth. This finding is consistent with those of previous studies in DH rabbits receiving antenatal sildenafil treatment 33 , in which lower PVR was attributed to an improvement in fixed structural factors such as the density of distal pulmonary blood vessels 25,29,31,33 . However, the magnitude of the difference in PVR between DH-sildenafil and DH-saline lambs increased after birth, which may reflect a greater vasodilatory response to lung aeration and ongoing ventilation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…PVR was lower in DH-sildenafil, compared with DH-saline, lambs during the fetal instrumentation period immediately before birth. This finding is consistent with those of previous studies in DH rabbits receiving antenatal sildenafil treatment 33 , in which lower PVR was attributed to an improvement in fixed structural factors such as the density of distal pulmonary blood vessels 25,29,31,33 . However, the magnitude of the difference in PVR between DH-sildenafil and DH-saline lambs increased after birth, which may reflect a greater vasodilatory response to lung aeration and ongoing ventilation.…”
Section: Discussionsupporting
confidence: 92%
“…We focused primarily on the physiological effects of antenatal sildenafil treatment in DH lambs, so our study is limited by the absence of histological evidence to confirm the morphological and biochemical features underlying the observed physiology. However, the effects of sildenafil on pulmonary vascular development have been well described in other animal models of CDH and correlate well with our current findings. Interestingly, fetal plasma sildenafil concentrations in our lambs immediately prior to delivery (2–5 ng/mL) were similar to those obtained in rats by Mous et al ,.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Luong et al [16] demonstrated that prenatally administered sildenafil in the nitrofen CDH model increased lung capillary density. Kattan et al [40] reported that phosphodiesterase-5 inhibitors may improve angiogenesis during pulmonary vascular development in CDH fetuses. Mous et al [12] demonstrated that prenatal sildenafil started at a clinically relevant time point decreases lung hypoplasia and attenuates vascular remodeling in nitrofen-induced CDH in rats.…”
Section: Discussionmentioning
confidence: 99%